Analysis on Supporting Stability for Track Subgrade Dynamic Response In-situ Test Device Based on NSGA-II - Feilong Zheng; Liangcai Zeng; Gangsheng Kai (Institute of Advanced Engineering and Science, 2013)
The dynamic response test to the subgrade plays a very important role in railway construction and a new in-situ test system is proposed. This paper presents the application of non-dominated sorting genetic algorithm-II (NSGA-II) to analyze the stability of the supporting equipment for track subgrade dynamic response in-situ test device. Its stability is related with the extension length of the hydraulic cylinders and the backward condition of the supporting equipment - the hydraulic excavator. The problem is formulated as a multi-objective optimization problem with the objective of maximizing the supporting force for the test device. An 85 tons excavator is picked as the case to study. The first optimal results show the excavator may not support the test system successfully. After redesigning the boom and adding its weight and length as new parameters, the second optimize results indicate the test device can work normally. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3986